ANALISIS PERBANDINGAN KINERJA KEUANGAN PADA PD BPR BKK KEBUMEN DAN PT BPR DANA MITRA SEJAHTERA KEBUMEN - Erma Reiza Damayanti; Dyah Fitriani (Universitas Ahmad Dahlan, 2015)
The research aims to comparehealth of BPR in terms of financial performance. The object of the research is PD BPR BKK Kebumen and PT BPR Dana Mitra Sejahtera for a period of 2012,2013 and 2014. Banking financial performance used on this research is on financial aspects that be measured by the ratio of the suffciency minimum obligation (CAR), the ratio of the quality of assets productive (KAP), an allowance the formation of productive assets (PPAP), the ratio return on assets (ROA) that reflect the ability of a bank in generate profit, the ratio of BOPO ( the load operational against operational income) that reflects the burden of operational compared with earnings obtained, while for liquidity measured by CR and LDR. From this research obtained the results of that overall shows the level of financial performance of a healthy. The ratio CAR in PD BPR BKK Kebumen shows the average 15,21% larger from PT BPR Dana Mitra Sejahtera that shows the average CAR 12,70% and both banks included in category of healthy. The rati of the quality of assets productive (KAP) in PD BPR BKK Kebumen shows the average 5,68% larger than PT Dana Mitra Sejahtera which shows the average quality of assets productive 5,27% and both banks included in category of healthy. The ratio of PPAP inPD BPR BKK Kebumenthat shows the average 100% and PT BPR Dana Mitra Sejahtera which shows the average 95,68% and both banks included in category of healthy. The ratio ROA in PD BPR BKK Kebumen shows the average 3,64% larger than PT BPR Dana Mitra Sejahtera which shows the the average ROA 2,24% and both banks included in category of healthy.the ratio of BOPO in PD BPR BKK Kebumen shows the average 72,13% less than than funds PT BPR Dana Mitra Sejahtera which shows the average BOPO 75,68% and both banks included in category of healthy. The ratio of CR in PD BPR BKK Kebumen shows the average 25,82% larger from PT BPR Dana Mitra Sejahtera thatshows the average CR 21,02% and both bank included in category of healthy. The ratio LDR in PD BPR BKK Kebumen shows the average 98,90% and included in category of less healthy and this is different from PT BPR Dana Mitra Sejahtera that Shows the average 78,33% in categories healthy. The ratio of non performing loan (NPL) in PD BPR BKK Kebumen shows the average 3,87% and dutifully included in the category of while from PT BPR Dana MitraSejahtera which shows the average NPL 5,25% greater than that required in category 5% so dutifully enough. Of a whole the assessment of the level second health BPR in PT BPR Dana Mitra Sejahtera it has value 99.90 % better than PD BPR BKK kebumen in that it has value 99.05 %.